AgBr/MgBi2O6 heterostructured composites with highly efficient visible-light-driven photocatalytic activity. (June 2018) - Zhong, Liansheng; Hu, Chaohao; Zhuang, Jing; Zhong, Yan; Wang, Dianhui; Zhou, Huaiying
Abstract: AgBr/MgBi2 O6 heterostructured photocatalysts were synthesized by the deposition-precipitation method. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), photoluminescence (PL), and UV–Visible diffuse reflectance spectroscopy (UV–Vis DRS) were employed to examine the phase structure, morphology and optical properties of the as-prepared samples. The photocatalytic activity was investigated by decomposing methylene blue (MB) solution under visible light irradiation (λ > 420 nm). AgBr/MgBi2 O6 composites exhibited significantly enhanced visible-light-driven photocatalytic properties in comparison with pure MgBi2 O6 and AgBr. When the molar ratio of AgBr to MgBi2 O6 was 3:1, the composite catalyst showed the optimal photocatalytic activity and excellent stability. The enhanced photocatalytic activity of AgBr/MgBi2 O6 composites was attributed to the formation of p-n heterojunction between AgBr and MgBi2 O6, thereby resulting in the effective separation and transfer of photogenerated electrons-hole pairs. Graphical abstract: AgBr/MgBi2 O6 composites with visible-light-driven photocatalytic activity were synthesized using the deposition-precipitation method. The significantly enhanced photocatalytic activity is ascribed to the formation of p-n heterojunction in AgBr/MgBi2 O6 composites. Highlights: AgBr/MgBi2 O6 composites with visible-light-driven photocatalytic activity were synthesized. AgBr/MgBi2 O6 (3:1) composite exhibits the highest visible-light photocatalytic activity. AgBr/MgBi2 O6 heterojunction shows excellent stability reusability. The formation of p-n heterojunction is responsible for the enhanced photocatalytic activity.